SELFHOOD AT THE FRAGILE BORDER OF (AB)NORMALITY - Attila KOVÁCS (Studia Universitatis Babeș-Bolyai. Philosophia)
Selfhood at the Fragile Border of (Ab)normality. We will attempt to briefly examine the phenomenological aspects of the ontic and ontological appearance of normal selfhood and psychopathological manifestations. Behind the psychological, anthropological or hermeneutical and cultural philosophical concepts relating selfhood one can discover the phenomenal character of the appearance of our identity within the domain of experience. Furthermore, towards the end of our study, we will employ specific phenomenological concepts, which we try to apply to different psychopathological manifestations. Our goal is to present a paradigm shift pertaining to the interpretation of abnormality and especially schizophrenia, which is made possible precisely by the phenomenological approach presented above.